2015
DOI: 10.3171/2014.9.spine14244
|View full text |Cite
|
Sign up to set email alerts
|

Spine fusion cross-link causing delayed dural erosion and CSF leak: case report

Abstract: The past 2 decades have seen a considerable increase in the number of lumbar spinal fusion surgeries. To enhance spinal stabilization and fusion, make the construct resistant to or stiffer for axial stress loading, lateral bending, and torsional stresses, cross-links and connectors were designed and included in a rod-screw construct. The authors present the case of a 49-year-old woman who presented 11 years after undergoing an L4–5 decompression and fusion in which a pedicle screw-rod construct with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Additionally, How et al [ 30 ] identified TC application as a risk factor for pseudojoint formation in orthopaedic surgery for spinal deformities. Rahmathulla et al [ 31 ] reported that TCs might contribute to spinal stenosis and delayed cerebrospinal fluid leakage. In our study, the use of TCs in TES did not significantly affect the ROM in the fixed segment or generate greater stress at the adjacent endplate.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, How et al [ 30 ] identified TC application as a risk factor for pseudojoint formation in orthopaedic surgery for spinal deformities. Rahmathulla et al [ 31 ] reported that TCs might contribute to spinal stenosis and delayed cerebrospinal fluid leakage. In our study, the use of TCs in TES did not significantly affect the ROM in the fixed segment or generate greater stress at the adjacent endplate.…”
Section: Discussionmentioning
confidence: 99%
“…PRES is characterized by postural headaches, altered mental status, seizures, and visual disturbances, all of which resolved after revision with dural repair (21). Additionally, Rahmathulla et al described a case of delayed dural erosion from a crosslink causing postural headaches 11 years after index surgery (22). …”
Section: Discussionmentioning
confidence: 99%
“…Cross-links were primarily planned to increase and maintain the stability of the coronal plane in long-segment scoliosis surgery [11][12][13]. They can increase axial stress loading, prevent lateral bending and rod migration, and minimize the total number of pedicle screws inserted in long-segment fixation [14][15][16].…”
Section: Plain Language Summarymentioning
confidence: 99%